Desenvolvimento e validação de método para determinação de resíduos de pesticidas em planta medicinal desidratada Hyptis pectinata utilizando DMFS e CG/EM - Aquino, Adriano (2011)
The Hyptis pectinata (L.) Poit is a medicinal plant widely used in the Sergipe state for the treatment of skin illnesses, gastric clutter, nasal congestion and inflammation caused for bacteria and fungi. Hyptis pectinata, as well as other medicinal plants, can be contaminated with pesticides that are used in the agriculture, and residues cause damages to the man and the environment, due the toxicity of these products. In Brazil values of maximum residue limits (LMR) have not yet been established for pesticides in medicinal plants. In a similar way, it has little information about to the degree of contamination of these phytotherapic resources. Therefore, analytical methods have been developed for determination of residues in medicinal plants, with intention to assure the health of the population. In this context, this work considered the development of an analytical method for the extraction of pyrimethanil, ametryn, dichlofluanid, tetraconazole, flumetralin, kresoxim-methyl and tebuconazole from the medicinal plant Hyptis pectinata using the matrix solid-phase dispersion (MSPD) and gas chromatography-mass spectrometry (GC/MS). Therefore, in the present study, the aim was evaluating the combinations adsorvent/solvent (silica gel, Florisil®, neutral alumina and coordination polymers [Zn(BDC)(H2O)2]n, CuBTC and MIL-53/dichloromethane, dichloromethane:ethyl acetate (1:1, v/v) and ethyl acetate), for the simultaneous extraction of these pesticides. Amongst the evaluated combinations, the on consisting of 0.5 g of C18 and 20 mL of dichloromethane was most efficient, getting recoveries between 85 and 127%, with relative standard between 4 and 15%, in the levels of concentration 0.05; 0.1; 0.5 and 1.0 μg g-1. The linearity was above 0.9987 and the limits of detection between 0.02 and 0.07 μg g-1 and of quantification, 0.05 and 0.1 μg g-1. Among the polymeric phases (CuBTC, MIL-53 and [Zn(BDC)(H2O)2]n), [Zn(BDC) (H2O)2]n was most efficient in the extraction of pyrimethanil (83%), ametrin (95%), dichlofluanid (90%), tetraconazole (81%), flumetralin (74%) and kresoximmethyl (94%), being therefore a viable alternative to the adsorvent commercial conventional C18.